Isolation and preliminary characterization of a phosphonoacetic acid-resistant and temperature-sensitive mutant of herpes simplex virus type 1. - Daksis, J I (1982)
A group of 43 phosphonoacetic acid (PAA)-resistant mutants of herpes simplex virus type 1 was isolated after the mutagenesis of infected cells with nitrosoguanidine. One of these mutants, designated PAA1rts1, was found to be temperature sensitive (ts), that is, unable to replicate at 39.5 degrees C, the nonpermissive temperature. Recombination analysis of PAA1rts1 indicated that the PAA1r mutation and the ts1 mutation are loosely linked and are located on two separate genes. PAA1rts1 showed a defect in viral DNA synthesis at 39.5 degrees C, which presumably can be attributed to the production of a PAA-resistant and thermolabile DNA polymerase. PAA1rts1 was also defective in the shutoff of host DNA synthesis at the restrictive temperature.